2013
DOI: 10.1093/ejcts/ezt050
|View full text |Cite
|
Sign up to set email alerts
|

Experience, outcomes and impact of delayed indication for video-assisted wide septal myectomy in 69 consecutive patients with hypertrophic cardiomyopathy†

Abstract: Clinical, haemodynamic and mortality outcomes after surgery were excellent, especially in those patients with mild or few symptoms. However, in our location, surgery is still undertaken at an advanced stage of the natural history of the disease, which may adversely affect prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Hence, our method cannot be considered “true” videoscope‐assisted myectomy. However, in our experience, this surgical technique is easier, safer, 11 and does not pose an additional risk.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Hence, our method cannot be considered “true” videoscope‐assisted myectomy. However, in our experience, this surgical technique is easier, safer, 11 and does not pose an additional risk.…”
Section: Discussionmentioning
confidence: 65%
“…Heredia Cambra et al 11 reported a similar method of myectomy using a rigid videoscope in all myectomy cases. However, in our opinion, there are downsides to VATAM.…”
Section: Discussionmentioning
confidence: 99%
“…Their technique has been partially developed previously using a rigid videoscope. 2 The authors state that this surgical technique is easier and, based on the paper of Heredia Cambra et al, also safer. 2 Our experience as a cardiac surgery center using a minimally invasive approach for all patients, leads us to commend Park and colleagues for their intent to make a procedure easier for the surgeon and, consequently, safer for the patient.…”
mentioning
confidence: 97%
“…2 The authors state that this surgical technique is easier and, based on the paper of Heredia Cambra et al, also safer. 2 Our experience as a cardiac surgery center using a minimally invasive approach for all patients, leads us to commend Park and colleagues for their intent to make a procedure easier for the surgeon and, consequently, safer for the patient. Unfortunately, what we surgeons sometimes "feel" in our hands in terms of simplicity and safety does not always translates into equivalent statistical inference.…”
mentioning
confidence: 97%
See 1 more Smart Citation